Study on a New Ignition Method of the Spark Gap Based on Plasma Ejection in Air. Issue 1 (12th September 2016) - Huang, D.; Yang, L.J.; Huo, P.; Ma, J.B.; Liu, S.; Wang, W.; Ding, W.D.
Abstract: A new ignition method of the spark gap based on plasma ejection is proposed in this paper, as the conventional trigatron spark gap performs poorly under the low working coefficient (the ratio of the charging voltage to the self‐breakdown voltage) in air. The plasma is generated by the capillary discharge, which has high pressure, high temperature and high velocity. The capillary discharge device is placed inside the low voltage electrode. As long as the triggering signal is sent to the device, a column of the plasma flow is ejected in axial direction and develops rapidly towards the high voltage electrode. Subsequently, the gap is broken down and a high resistive channel is formed, where the thermal ionization takes place and the arc across the whole gap is generated and develops into a well conductive channel. The process of the thermal ionization of the high resistive channel varies with the change of the spark gap distance. The breakdown delay and the delay jitter of the spark gap increase with the spark gap distance, as both parameters are mainly determined by the developing process of the plasma ejection. The characteristics of the plasma flow determine the possibility of the breakdown of the spark gap under the low working coefficient. The ignition method based on capillary plasma ejection has been proved by the preliminary experiments, which indicate that under the gap length of 8 cm and the working coefficient of less than 3%, the effective ignition is still achievable.